Lectotypification of Arundo roraimensis, the basionym of Cortaderia roraimensis (Poaceae—Danthonioideae) - de Oliveira, Reyjane Patricia; Dórea, Marcos Da Costa; Welker, Cassiano Aimberê Dorneles (Phytotaxa, 2016)
The genus Cortaderia Stapf (1897: 378, 396) is a member of the grass subfamily Danthonioideae and includes, in its current delimitation, 20 species restricted to South America (Linder et al. 2010, Kellogg 2015). The individual plants in this genus are gynodioecious, either entirely pistillate or with bisexual flowers (Kellogg 2015).